2016
DOI: 10.1038/ncomms11150
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal transfer of stroma-derived miR21 confers paclitaxel resistance in ovarian cancer cells through targeting APAF1

Abstract: Advanced ovarian cancer usually spreads to the visceral adipose tissue of the omentum. However, the omental stromal cell-derived molecular determinants that modulate ovarian cancer growth have not been characterized. Here, using next-generation sequencing technology, we identify significantly higher levels of microRNA-21 (miR21) isomiRNAs in exosomes and tissue lysates isolated from cancer-associated adipocytes (CAAs) and fibroblasts (CAFs) than in those from ovarian cancer cells. Functional studies reveal tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
563
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 625 publications
(590 citation statements)
references
References 40 publications
13
563
0
Order By: Relevance
“…Moreover, it has been shown that exosomes can be secreted by CAFs and taken up by cancer cells, as isolated exosomes from primary CAFs transfected with labeled miR‐21 successfully entered ovarian cancer cells (Au Yeung et al ., 2016). They confirmed transfer of miR‐21 from primary CAFs to ovarian cancer cells by co‐culturing CAFs transfected with labeled miR‐21 with ovarian cancer cells (Au Yeung et al ., 2016). In addition, miR‐21 was frequently upregulated in CAFs from both human pancreatic ductal adenocarcinoma samples and primary cell cultures, and higher expression of miR‐21 was significantly correlated with decreased overall survival in pancreatic ductal adenocarcinoma patients (Donahue et al ., 2014; Kadera et al ., 2013).…”
Section: Transfer Of Biological Information Between Tumor Microenviromentioning
confidence: 99%
“…Moreover, it has been shown that exosomes can be secreted by CAFs and taken up by cancer cells, as isolated exosomes from primary CAFs transfected with labeled miR‐21 successfully entered ovarian cancer cells (Au Yeung et al ., 2016). They confirmed transfer of miR‐21 from primary CAFs to ovarian cancer cells by co‐culturing CAFs transfected with labeled miR‐21 with ovarian cancer cells (Au Yeung et al ., 2016). In addition, miR‐21 was frequently upregulated in CAFs from both human pancreatic ductal adenocarcinoma samples and primary cell cultures, and higher expression of miR‐21 was significantly correlated with decreased overall survival in pancreatic ductal adenocarcinoma patients (Donahue et al ., 2014; Kadera et al ., 2013).…”
Section: Transfer Of Biological Information Between Tumor Microenviromentioning
confidence: 99%
“…Further characterization of the feedback loops initiated by EVs on tumor cells and the stromal environment might provide critical missing pieces in this picture. In a different context CAF EVs with increased levels of miRNA-21 profoundly impact ovarian cancer growth by suppressing apoptosis through binding to its novel target, APAF1 7 . Finally, as discussed above CAF-derived EVs directly participate in metabolic reprogramming.…”
Section: Evs Reprogram Cancer Cell Metabolismmentioning
confidence: 99%
“…Cancer-associated fibroblasts (CAFs), one of the primary stromal cell types in ovarian tumor tissues (6), secrete CAF-specific proteins, cytokines, and growth factors and produce an extracellular matrix (ECM) that supports tumor cell growth and angiogenesis and confers chemoresistance (7)(8)(9)(10)(11). However, the mechanisms by which CAFs promote angiogenesis in ovarian cancer remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%